PENGARUH STRATEGI MARKETING TERHADAP KEPUASAN PELANGGAN YANG DILAKUKAN KFC DI MASA PANDEMI COVID-19 - Dian Sudiantini; Ardhita Indah Cahyani; Ashraff Rizky Setyawan; Risma Felisyana; Zidan Hoerul Mutazam (Jurnal Bina Bangsa Ekonomika, 2023)
This study aims to find out what steps were taken by one of the fast food giants in Indonesia in maintaining its business during the Covid-19 pandemic and as learning material for readers on how to maintain a business in the midst of the Covid-19 pandemic. Positive customer satisfaction has a significant impact on customer loyalty. As customer satisfaction increases, customer loyalty to the products offered also increases. By reading our research, readers will get additional references on how to carry out a good and correct marketing strategy in the midst of the Covid-19 pandemic and by reading our research, readers will realize that it is important to maintain product quality in order to maintain stability in doing business